(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Translation is the process of conveying information from one language to another as accurately and comprehensively as possible. This requires the translator to introduce structural and semantic changes to account for differences in vocabulary, grammar, and cultural context between languages. These changes, referred to as transformations in translation, are necessary to ensure that the meaning of the original text is faithfully preserved in the translated version.